Jurisprudence - Ratnapala, Suri 1947- (New York Cambridge University Press, 2013)
Jurisprudence offers a comprehensive overview of legal theory and philosophy. Written in plain English, it examines and demystifies the discipline's major ideas, promoting a deeper understanding of the social, moral and economic dimensions of the law. Suri Ratnapla from University of Queensland
Law as it is-- Law and morality-- Social dimensions of law-- Rights and justice.
Includes bibliographical references (pages 399-408) and index.
Keywords: Law -- Philosopy; Jurisprudence